2010
DOI: 10.1093/humrep/deq060
|View full text |Cite
|
Sign up to set email alerts
|

Women who gave birth to girls with Turner syndrome: maternal and neonatal characteristics

Abstract: Advanced maternal age and short stature were risk factors for giving birth to a girl with TS. More TS girls were born late preterm and were smaller for gestational age than non-TS girls in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
6
14
1
Order By: Relevance
“…Classic associations between advancing age and chromosomally abnormal products of conception are demonstrated in this group. The link between younger age and monosomy X is reaffirmed in our study population [5]. Assisted reproduction technologies, such as ICSI, have been suggested to lead to higher rates of chromosomal abnormalities, however in this study ICSI (69 % vs. 72 % p00.76) did not affect the rate of genetically abnormal products of conception [2,7].…”
Section: Discussionsupporting
confidence: 71%
“…Classic associations between advancing age and chromosomally abnormal products of conception are demonstrated in this group. The link between younger age and monosomy X is reaffirmed in our study population [5]. Assisted reproduction technologies, such as ICSI, have been suggested to lead to higher rates of chromosomal abnormalities, however in this study ICSI (69 % vs. 72 % p00.76) did not affect the rate of genetically abnormal products of conception [2,7].…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have reported different effects on birth anthropometric data in TS patients (24,26,27), and some of these studies found no association with karyotype subgroup (27), probably due to the limited number of subjects studied. In two studies, BW was shown to be more affected in patients monosomic for the SHOX gene than in patients disomic for this gene (24,26). A detailed analysis of all anthropometric data as a function of GA extended our understanding of the impact of karyotype subgroup in TS on fetal growth, in terms of BW, BL, and head circumference.…”
Section: European Journal Of Endocrinologymentioning
confidence: 92%
“…Some authors have reported more severe spontaneous growth deficits in patients with monosomy of the short arm of the X chromosome than in those with disomy (11,21,22,23,24,25,26). Others found no significant difference in height between several karyotype subgroups (27,28,29).…”
Section: Introductionmentioning
confidence: 99%
“…For all individuals, we used the highest available education level and socioeconomic position as registered until 2009 (in children, we used the highest available parental level of education and socioeconomic position). 24 Using data from the Medical Birth Register, we included maternal age at delivery as a potential confounder because advanced maternal age at delivery has been positively associated with offspring TS 25 and may also be associated with offspring CD. 26 Type 1 diabetes is associated with TS 7 and CD.…”
Section: Covariatesmentioning
confidence: 99%
“…In our sample, the median age at TS diagnosis was 6 years, which is similar to that found in a previous Swedish study. 25 The finding of a relatively high risk of CD among females aged >10 years could also reflect the challenges to clinically recognize CD in very young females with TS. Previous research on TS has shown that subclinical CD is common and that those with symptomatic CD, despite a high level of suspicion, frequently face long diagnostic delays.…”
Section: Interpretation Of Findings and Previous Literaturementioning
confidence: 99%